The future we want: Participatory workshops in Kenya's Nandi County - Habermann, Birgit; Kumar, Praveen; Kibet, Walter; Mwambi, Diana (CGIAR, 2023)
On November 14 and November 23, 2023, the Living Lab for People (LL4P) at Kaimosi Agricultural Training Centre (KATC) organized two workshops with different stakeholders to develop a vision for a Sustainable and Low-Emission Food System for Nandi County. The aim of the workshops was twofold: 1) To understand both the present image and the future vision of the Nandi County Food System citizens of different stakeholder groups and in relation to lowering emissions in the food system, and 2) To understand the meaning of low-emission food systems for the stakeholders, and factors impacting low-emission food systems in the Nandi County. The first week, it was government, NGO and private sector stakeholders, the second week farmers, farmer groups and cooperatives, representing also women and youth in agriculture. The participants were purposively selected based on a desk review to uncover key stakeholders, who are instrumental in the food system of Nandi County. These organizations and individuals were invited to participate because of their role in the food system of Nandi County.